Factors Influencing the Performance of Nurses and Midwives at Jimmy Medika Borneo Mother and Child Hospital - Andik Supriyatno; Dwi Ida Puspita Sari; Muksin Muksin; Nur Asiza; Muhammad Henry Gunawan (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2021)
The task of health workers is to organize or organize quality health services in accordance with their expertise and / or competence, one of which is nurses. Hospitals are one part of the health care system that plays an important role in improving the degree of public health. This study aims to find out what factors affect the performance of nurses and midwives at Jimmy Medika Borneo mother and child hospital. This research is a quantitative research with a cross-sectional approach. The samples in this study were nurses and midwives whose total sample was 45 people. The variables measured in this study are human resources, finances, knowledge, leadership and communication. The results showed that there was an influence of human resources (p = 0.00), financial (p = 0.0 3), knowledge (p = 0.0 4), leadership (p = 0.02 4) and communication (p = 0.03) on the performance of nurses in carrying out nursing and midwifery services.